Dynamic Functional Connectivity Patterns in Schizophrenia and the Relationship With Hallucinations - Weber, Sarah; Johnsen, Erik; Kroken, Rune A.; Løberg, Else-Marie; Kandilarova, Sevdalina; Stoyanov, Drozdstoy; Kompus, Kristiina; Hugdahl, Kenneth (Frontiers in Psychiatry, 2020)
There is a wealth of evidence showing aberrant functional connectivity (FC) in schizophrenia but with considerable variability in findings across studies. Dynamic FC is an extension of traditional static FC, in that such analyses allow for explorations of temporal changes in connectivity. Thereby they also provide more detailed information on connectivity abnormalities in psychiatric disorders such as schizophrenia. The current study investigated dynamic FC in a sample of 80 schizophrenia patients and 80 matched healthy control subjects, replicating previous findings of aberrant dwell times in specific FC states, and further supporting a role for default mode network (DMN) dysfunction. Furthermore, relationships with auditory verbal hallucinations (AVH), a core symptom of schizophrenia, were explored. Two measures of AVH were used, one state-measure where AVH severity was assessed on the day of scanning, and one trait-measure where AVH were assessed repeatedly over the course of one year. State-derived AVH severity did not show a significant relationship with dynamic FC. However, the trait-measure of AVH proneness over one year showed a significant relationship with dynamic FC. Patients with high AVH proneness spent less time in connectivity states characterized by strong anti-correlation between the DMN and task-positive networks. The findings support theoretical models of AVH which have proposed an instability of the DMN and impaired cognitive control in AVH patients. Furthermore, the results point to AVH proneness as a potential marker for identifying distinct subgroups of schizophrenia patients.